2007
DOI: 10.1097/bsd.0b013e3180335bf7
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage Posterolateral Vertebrectomy for the Management of Metastatic Disease of the Thoracic and Lumbar Spine

Abstract: Appropriate surgical management of spinal metastases combines maximal neural decompression with simultaneous immediate spinal column stabilization in the context of a paliative operation undertaken to improve patients' quality of life. We have used a single-stage posterolateral vertebrectomy (SPLV) for disease of the lumbar spine, combined with bilateral costotransversectomies in the thoracic spine, for these challenging cases. In this prospective cohort study of 96 consecutive patients with metastatic disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
63
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 27 publications
1
63
0
3
Order By: Relevance
“…Street et al [13] reported that out of 37 patients with ASIA cord deficit, who underwent a single-stage posterolateral vertebrectomy, nearly half of the patients improved one ASIA grade at the end of the follow-up. All the patients presented with an isolated root deficit and a single patient who was presented with Cauda Equina syndrome had made a complete recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Street et al [13] reported that out of 37 patients with ASIA cord deficit, who underwent a single-stage posterolateral vertebrectomy, nearly half of the patients improved one ASIA grade at the end of the follow-up. All the patients presented with an isolated root deficit and a single patient who was presented with Cauda Equina syndrome had made a complete recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Three patients (3/134, 2.2 %) died from complications. In a series of 42 patients, who underwent the posterolateral vertebrectomy approach reported by street et al [13], 20 patients suffered with one or more complications for an overall patient complication rate of 47 %. Eleven patients had a major complication (26 %).…”
Section: Discussionmentioning
confidence: 99%
“…Because of their immunocompromised [17,30,33,34]. For these patients with limited life expectancies, the appropriate treatment is to achieve relief of pain and to regain function, thus improving the quality of the life as quickly as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Street et al 17 reported on 66 patients undergoing either anterior-posterior (24 cases) and posterolateral (42 cases) corpectomies for metastatic disease, with an overall complication rate of 47%. They found that EBL was significantly higher in anterior-only or anteriorposterior corpectomies compared with posterolateral corpectomies.…”
Section: Discussionmentioning
confidence: 99%